Contrasting altitudinal variation of alpine plant communities along the Swedish mountains. Issue 11 (16th April 2020) - Måsviken, Johannes; Dalerum, Fredrik; Cousins, Sara A. O.
Abstract: Changes in abiotic factors along altitudinal and latitudinal gradients cause powerful environmental gradients. The topography of alpine areas generates environmental gradients over short distances, and alpine areas are expected to experience greater temperature increase compared to the global average. In this study, we investigate alpha, beta, and gamma diversity, as well as community structure, of vascular plant communities along altitudinal gradients at three latitudes in the Swedish mountains. Species richness and evenness decreased with altitude, but the patterns within the altitudinal gradient varied between sites, including a sudden decrease at high altitude, a monotonic decrease, and a unimodal pattern. However, we did not observe a decline in beta diversity with altitude at all sites, and plant communities at all sites were spatially nested according to some other factors than altitude, such as the availability of water or microtopographic position. Moreover, the observed diversity patterns did not follow the latitudinal gradient. We observed a spatial modularity according to altitude, which was consistent across sites. Our results suggest strong influences of site‐specific factors on plant community composition and that such factors partly may override effects from altitudinal and latitudinal environmental variation. Spatial variation of the observed vascular plant communities appears to have been caused by a combination of processes at multiple spatial scales. Abstract : We studied the altitude variation of alpine plant communities in the Swedish mountains. We found that species richness and evenness decreased with altitude but the patterns within the altitude gradient varied between sites, including a sudden decrease at high altitude, a monotonic decrease, and a unimodal pattern.